Synergistic Configuration of Binary Rhodium Single Atoms in Carbon Nanofibers for High‐Performance Alkaline Water Electrolyzer - Natarajan Logeshwaran; Gyuchan Kim; Pandiarajan Thangavel; Sun Seo Jeon; Kaliannan Thiyagarajan; Kampara Roopa Kishore; Hyunjoo Lee; Inseok Seo; Hongseok Yun; Sungho Lee; Byung‐Hyun Kim; Young Jun Lee (Advanced Science)
Abstract Electrochemical alkaline water electrolysis offers significant economic advantages; however, these benefits are hindered by the high kinetic energy barrier of the water dissociation step and the sluggish kinetics of the hydrogen evolution reaction (HER) in alkaline media. Herein, the ensemble effect of binary types of Rh single atoms (Rh‐Nx and Rh‐Ox) on TiO2‐embedded carbon nanofiber (Rh‐TiO2/CNF) is reported, which serves as potent active sites for high‐performance HER in anion exchange membrane water electrolyzer (AEMWE). Density functional theory (DFT) analyses support the experimental observations, highlighting the critical role of binary types of Rh single atoms facilitated by the TiO2 sites. The Rh‐TiO2/CNF demonstrates an impressive areal current density of 1 A cm−2, maintaining extended durability for up to 225 h in a single‐cell setup. Furthermore, a 2‐cell AEMWE stack utilizing Rh‐TiO2/CNF is tested under industrial‐scale conditions. This research makes a significant contribution to the commercialization of next‐generation high‐performance and durable AEMWE stacks for clean hydrogen production.